Designing the causal model of job attachment based on social support and job independence with a mediating role of job self-efficacy among the staff of a military hospital - Zhara Sharafi; Maryam Akbari; Hamzeh Ahmadian; Rafigh Hassani (فصلنامه ابن سینا)
Background: Staff at Armed Forces Medical Centers are more at risk of job burnout, and their job attachment is affected because of the special conditions of their relevant organization. Therefore, the aim of this study was to develop and design the causal model of job attachment based on social support and job independence with the mediating role of job self-efficacy. Materials and methods: This descriptive correlational study was an applied one that was performed in 2019 on 275 employees of a military hospital who were selected through stratified random sampling. Data was collected from job attachment questionnaires, social support, job independence, and job self-efficacy. Data were analyzed using Structural Equation Modeling (LISREL software) and multivariate analysis of covariance (ANCOVA) using SPSS software. Results: The significant coefficient of social support with the moderating effects of job self-efficacy in job attachment was 0.142. Additionally, the significant coefficient of job independence with the moderating effects of job self-efficacy was 0.191 in job attachment. Conclusion: Based on the present research, it can be inferred that psychological characteristics play an important role in job attachment.